2013
DOI: 10.1097/mbc.0b013e3283610396
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of elevated D-dimer in patients undergoing primary angioplasty for ST elevation myocardial infarction

Abstract: The aim of this study was to evaluate the prognostic value of D-dimer in patients with STEMI undergoing primary percutaneous coronary intervention (PCI). The prognostic value of D-dimer has been documented in patients with acute coronary syndrome without ST-segment elevation. However, its value in acute ST-segment elevation myocardial infarction (STEMI) remains unclear. We prospectively enrolled 453 consecutive STEMI patients (mean age 55.6 ± 12.4 years, 364 male, 89 female) undergoing primary PCI. The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Furthermore, DD was found to be associated with poor outcomes in patients with AMI. Akgul O et al [10] demonstrated that a high admission DD level (>0.72 ug/ml FEU) was a powerful independent predictor of 6-month allcause mortality. Another study of HORIZONS-AMI trial[38] showed admission DD levels were a strong predictor of MACE in patients treated with pPCI within 3 years follow up.Compared with patients with lower DD levels(<0.71 ug/ml), patients with higher DD levels(≥0.71 ug/ml) on admission were associated with an adjusted hazard ratio of 2.58 for MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DD was found to be associated with poor outcomes in patients with AMI. Akgul O et al [10] demonstrated that a high admission DD level (>0.72 ug/ml FEU) was a powerful independent predictor of 6-month allcause mortality. Another study of HORIZONS-AMI trial[38] showed admission DD levels were a strong predictor of MACE in patients treated with pPCI within 3 years follow up.Compared with patients with lower DD levels(<0.71 ug/ml), patients with higher DD levels(≥0.71 ug/ml) on admission were associated with an adjusted hazard ratio of 2.58 for MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DD was found to be associated with poor outcomes in patients with AMI. Akgul O et al [10] demonstrated that a high admission DD level (>0.72 ug/ml FEU) was a powerful independent predictor of 6-month allcause mortality. Another study of HORIZONS-AMI trial [38] showed admission DD levels were a strong predictor of MACE in patients treated with pPCI within 3 years follow up.Compared with patients with lower DD levels(<0.71 ug/ml), patients wiht higher DD levels(≥0.71 ug/ml) on admission were associated with an adjusted hazard ratio of 2.58 for MACE.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, DD had been reported to be a marker for the early diagnosis of ACS presenting with chest pain [8] and acute myocardial infarction (AMI) [9] . Furthermore, DD had been found to be associated with short-, mid-and long-term poor outcomes in patient with AMI [10][11][12] . In addition, as a marker of increased coagulability and fibrinolysis, DD also had been documented to be associated with renal insufficiency, which indicated that DD concentration increased significantly with increasing creatinine levels [13] or decreasing estimated glomerular filtration rate(GFR) [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences show that cys C is associated with cardiovascular risk and mortality in patients with non‐ST elevated acute coronary syndrome and is the most powerful predictor for major adverse cardiac events in patients with acute coronary syndrome . Akgul et al have investigated the predictive value of elevated cys C in STEMI patients undergoing primary PCI, and have found that the elevated cys C level, rather than the creatinine level nor eGFR, was an independent predictor of increased in‐hospital and 1‐month cardiac mortality in patients with STEMI undergoing primary PCI . Tang et al have found that elevated cys C levels at admission were independently associated with impaired myocardial perfusion, poor cardiac functional recovery, and development of congestive heart failure in these patients .…”
Section: Discussionmentioning
confidence: 99%